Respuesta :
Answer:
The population of four years ago was 100,783 inhabitants
Step-by-step explanation:
The population of the city after t years is given by the following equation:
[tex]P(t) = P(0)(1-r)^{t}[/tex]
In which P(0) is the initial population and r is the decrease rate, as a decimal.
2 years later, that is to say two years ago, the population of this same city was 81,000 inhabitants and today it is 65,610.
This means that:
[tex]P(2) = 81000, P(4) = 65610[/tex]
We are going to use this to build a system, and find P(0), which is the initial population(four years ago).
P(2) = 81000
[tex]P(t) = P(0)(1-r)^{t}[/tex]
[tex]81000 = P(0)(1-r)^{2}[/tex]
[tex](1-r)^{2} = \frac{81000}{P(0)}[/tex]
P(4) = 65610
[tex]P(t) = P(0)(1-r)^{t}[/tex]
[tex]65100 = P(0)(1-r)^{4}[/tex]
[tex]65100 = P(0)((1-r)^{2})^{2}[/tex]
Since [tex](1-r)^{2} = \frac{81000}{P(0)}[/tex]
[tex]65100 = P(0)(\frac{81000}{P(0)})^{2}[/tex]
Using P(0) = x
[tex]65100 = x(\frac{81000}{x})^{2}[/tex]
[tex]65100 = \frac{6561000000x}{x^{2}}[/tex]
[tex]65100x^{2} = 6561000000x[/tex]
[tex]65100x^{2} - 6561000000x[/tex]
[tex]x(65100x - 6561000000) = 0[/tex]
x = 0, which does not interest us, or:
[tex]65100x - 6561000000 = 0[/tex]
[tex]65100x = 6561000000[/tex]
[tex]x = \frac{6561000000}{65100}[/tex]
[tex]x = 100,783[/tex]
The population of four years ago was 100,783 inhabitants